2019
DOI: 10.3390/ijms20061450
|View full text |Cite
|
Sign up to set email alerts
|

DFT Studies on the Antioxidant Activity of Naringenin and Its Derivatives: Effects of the Substituents at C3

Abstract: The radical scavenging activity of a flavonoid is largely influenced by its structure. The effects of the substituents at C3 position on the antioxidant activity of naringenin were carried out using the density functional theory (DFT) method. The reaction enthalpies related with the three well-established mechanisms were analyzed. Excellent correlations were found between the reaction enthalpies and Hammett sigma constants. Equations obtained from the linear regression can be helpful in the selection of suitab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 42 publications
1
27
0
Order By: Relevance
“…Catechin (3,3′,4′,5,7-pentahydroxyflavan) is a compound commonly found in several types of green tea, cocoa, red grapes and onions [ 49 , 120 , 131 , 132 , 133 ]. It also can be found and isolated from A. schoenoprasum [ 62 ].…”
Section: Structure-antioxidant Activity Relationship Compounds In Alliummentioning
confidence: 99%
“…Catechin (3,3′,4′,5,7-pentahydroxyflavan) is a compound commonly found in several types of green tea, cocoa, red grapes and onions [ 49 , 120 , 131 , 132 , 133 ]. It also can be found and isolated from A. schoenoprasum [ 62 ].…”
Section: Structure-antioxidant Activity Relationship Compounds In Alliummentioning
confidence: 99%
“…Different computational approaches have been used to investigate flavonoid structures. 3 , 31 , 37 , 38 Recently, Zheng et al performed a comparative study focusing on the interactions of the hydrogens in the solvated systems of 5,7-dihydroxy-2-(3,4-dihydroxyphenyl)-chrome-4-one (luteolin) using DFT (B3LYP method) and concluded that luteolin presents a nonplanar conformation. 37 Similarly, Matteini et al.…”
Section: Resultsmentioning
confidence: 99%
“…Many therapeutic agents have been identified in medicinal plants. However, some of these medicinal plants might contain a wide variety of chemical compounds, often with undetermined biological properties [ 62 ]. The antioxidant activities of polyphenolic compounds depend upon their ability to resist harmful effects of free radical species.…”
Section: Resultsmentioning
confidence: 99%